Dolly Bear Shop / Mohd Nor Hafizie Othman ... [et al.] - Othman, Mohd Nor Hafizie; Jidel@Jaidel, Norazrini; Jelani, Mohd Rizal; Mat Ghani, Mohd Fais; Omar, Mohd Amirul Adib (Faculty of Civil Engineering, 2006)
After we have a big discussion, finally we decide to choose the type of business is in state of a partnership business because it is a starting point to establish a business.Our company name is 'DOLLY BEAR SHOP' where the chosen based on our product, because we planned to sell the kind of soft toys which is dolls and bears. Since our business is partnership, so our ownership structure revolves among shareholders of members.This business owned by 5 members of us and each of us play an important role to ensure this business achieving the target and mission.Our director is known as General Manager and followed by 4 managers which is Administrative Manager, Marketing Manager, Operation Manager and Financial Manager who is responsible to supervise and to make sure the business run smoothly with strong financial condition so that we can maintain our business and make our shop famous.